Results of esophageal cancer treatment at National cancer institute 2008–2017 years - Zaremba, Sigitas; Aškinis, Renatas; Piščikaitė, Agota; Smailytė, Giedrė; Cicėnas, Saulius (Lietuvos chirurgija, 2019)
Introduction. Esophageal carcinoma is the eighth most common cancer, and the sixth most common cause of cancer related deaths worldwide. Despite many advances in diagnosis and treatment, the 5-year survival rate for all patients with esophageal cancer ranges from 15% to 20%. Our aim was to analyze these patients results of operative, conservative and palliative treatment, determine the survival rate at the National Cancer Institute (NCI) since 2008 to 2017. Methods. From 2008 to 2017, 512 patients with esophageal cancer were treated in NCI. Patients received operative, palliative operative treatment, chemoradiotherapy, radiotherapy, chemotherapy or symptomatic treatment. Statistical analysis was performed using STATA 11 statistical software. Results. 512 patients (mean age 61.8 years) were analyzed: 63 women (12.3%) and 449 men (87.7%). 25 patients (4.9%) had I stage cancer, II stage – 74 (14.4%), III stage – 258 (50.4%), IV stage – 155 (30.3%). The prevalent morphology – squamous cell carcinoma – 445 cases (86.9%) and adenocarcinoma – 48 cases (9.4%). There were 75 (14.6%) patients who underwent radical operations and 271 – palliative operations. Chemoradiotherapy was applied in 97 (19.0%) patients, radiotherapy – 81 (15.8%), chemotherapy – 111 (21.7%), symptomatic treatment – 148 (28.9%). After radical operations, the rate of complications was 46.17% and mortality was 10.67%. The most common complication – fistula. Overall survival: 1 y – 33.91%, 5 y – 9.0%. Depending on the type of treatment, 5 y survival: after radical surgery – 26.53%, after chemoradiotherapy – 17.95%, after radiotherapy – 5.36%, after chemotherapy – 1.92%, after symptomatic treatment – 1.92%. Conclusions. In the radical surgical treatment group, the incidence of postoperative complications was 46.17% and mortality rate – 10.67%. In the palliative surgical treatment group, the incidence of postoperative complications was 4.5% and mortality rate – 0.7%. 5 year overall survival rate at the National Cancer Institute was 9.0%. Important influence on survival rate had treatment modality, stage of disease and size of primary tumor.
Keywords: esophageal cancer; surgical treatment; complications; survival rate